Migrant labour and related issues - Joshī, Vidyuta; Gandhi Labour Institute, Ahmedabad; National Seminar on Migrant Labour and Related Issues (1985 : Gandhi Labour Institute, Ahmedabad) (New Delhi : Oxford & IBH Pub. Co., 1987)
Revised papers presented at the National Seminar on Migrant Labour and Related Issues, held at Gandhi Labour Institute, Ahmedabad, India, in October 1985.
Includes bibliographies and index.
Keywords: Migrant labor -- India -- Congresses; Rural-urban migration -- India -- Congresses